RAN potentiates nuclear export of phosphorylated AMPK, reshaping lipid metabolism and impairing immune efficacy in lung adenocarcinoma - Qingwu Du; Rui Li; Jian Wang; Jingya Wang; Yantao Jiang; Qi Xu; Dingzhi Huang; Tingting Qin (npj Precision Oncology)
Abstract The therapeutic effectiveness of immune checkpoint inhibitors (ICIs) in lung cancer remains constrained and demonstrates substantial variability across different patients. Targeting the metabolism of tumors emerges an encouraging strategy to enhance the outcomes of tumor immunotherapy. We analyzed metabolic differences in lung cancer post-anti-PD-1 treatment using a single-cell RNA sequencing data (n = 15). Abnormal lipid metabolism is notable in patients with a non-major pathological response, and low RAN expression is linked to good immunotherapy response. RAN showed increased expression in lung adenocarcinoma (LUAD) versus normal lung tissues, correlating with worse prognosis, advanced staging, reduced immune cell activity, and greater sensitivity to common chemotherapeutic drugs. Knockdown of RAN caused G2/M phase arrest, inhibiting proliferation and clone formation in LUAD cells. RAN modifies lipid metabolism via nuclear p-AMPK output to aid tumor cells in resisting immunotherapy and reduces MHC-related molecule expression to evade CD8 + T cell detection. Combining Selinexor with immunotherapy might effectively counter immune tolerance and boost anti-tumor responses in LUAD.